The Personality of the Speaker of T.S. Elliot’s “Portrait of a Lady” - Nia Susanti (Lexicon, 2012)
This research discusses the personality of the speaker of TS Eliot‘s “Portrait of a Lady”. The objective of this graduating paper is to find the speaker‘s personality as seen in his attitude toward the lady. The psychological approach is applied in this research to analyze the personality of the speaker. The analysis explains about the speaker‘s attitude toward the lady by interpreting the data as the primary data. The result is that he has good attitude and he has a good personality. He is firm with his decision not to have an intimate relationship with the lady which is forbidden by their different social status. Although they have mutual feelings, the speaker restrains his feeling of love toward the lady and leaves her at the end of the poem.